2015
DOI: 10.1002/2015gc005988
|View full text |Cite
|
Sign up to set email alerts
|

Improving shallow‐water carbonate chemostratigraphy by means of rudist bivalve sclerochemistry

Abstract: Deep-time shallow-marine carbonate platforms record distinct biotic responses to climatic and environmental stressors. Unfortunately, precise temporal assignment of these biotic responses is often problematical due to poor biostratigraphic control and/or a significant diagenetic overprint of the neritic bulk carbonate chemostratigraphic inventory. An accurate stratigraphic framework is essential to better understand the causal relation between biotic events recorded by carbonate platforms and environmental cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 89 publications
0
19
0
Order By: Relevance
“…A cross plot in Figure a shows that this correlation is moderate in strength ( R 2 = 0.47) and highly statistically significant ( p ≪ 0.05). Note that positive correlations between δ 13 C and δ 18 O records have been put forward by previous authors as evidence for disequilibrium fractionation and signs of diagenetic alteration (e.g., Huck & Heimhofer, ; McConnaughey, ; Steuber, ). However, the evidence cited above (see also Figure ) shows that stable isotope samples originated from the most pristine parts of the T. sanchezi outer shell layer, rendering diagenetic alteration unlikely.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…A cross plot in Figure a shows that this correlation is moderate in strength ( R 2 = 0.47) and highly statistically significant ( p ≪ 0.05). Note that positive correlations between δ 13 C and δ 18 O records have been put forward by previous authors as evidence for disequilibrium fractionation and signs of diagenetic alteration (e.g., Huck & Heimhofer, ; McConnaughey, ; Steuber, ). However, the evidence cited above (see also Figure ) shows that stable isotope samples originated from the most pristine parts of the T. sanchezi outer shell layer, rendering diagenetic alteration unlikely.…”
Section: Resultsmentioning
confidence: 68%
“…Since the rudists became extinct at the Cretaceous‐Paleogene boundary (Steuber et al, ), no close living relatives are available for comparison. As a result, even though rudist taxa have featured in several sclerochronology and geochemistry studies (e.g., Al‐Aasm & Veizer, , ; Gili et al, ; Gili & Götz, ; Huck & Heimhofer, ; Ross & Skelton, ; Skelton, ; Steuber, , ; Steuber et al, ), several aspects of their paleobiology remain uncertain. This uncertainty limits the potential of rudist shells as geochemical archives for climate and environmental change during the Cretaceous.…”
Section: Introductionmentioning
confidence: 99%
“…). Although the elemental and isotopic composition of biogenic hard parts (Immenhauser et al ., ; Schöne, ) are known to severely depend on metabolic processes, previous studies have shown that bivalve shells might act as a suitable archive for mid‐Cretaceous secular carbon isotope changes (Huck et al ., ; Huck & Heimhofer, ). Unfortunately, the petrographic inspection of bivalve shell fragments derived from the Jabal Madar section provides clear evidence for a moderate recrystallization and partial silicification of the fibrous low‐Mg calcite ultrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…10. Carbon isotope based correlation of the 'filtered' Jabal Madar record with age-calibrated neritic (Cluses) and basinal (Angles, Gorgo a Cerbara) reference records Sprovieri et al, 2006;Huck et al, 2011;Stein et al, 2011;Huck & Heimhofer, 2015). Note extremely low Barremian carbonate preservation rates as calculated from the Jabal Madar section.…”
Section: Integrated Barremian-aptian Shallow-water Stratigraphy Of Nomentioning
confidence: 99%
“…). The strontium concentration between 9·8 m and 60·5 m varies between 1000 and 1200 ppm (Table ) which is typical for biogenic low‐Mg calcite from rudist shells of the same age (Steuber & Veizer, ; Huck et al ., ; Huck & Heimhofer, ). The uppermost 20 m of the lower Huwar 2 Member (75 to 95 m) consist of micritic limestone with low strontium concentrations of 500 to 700 ppm.…”
Section: Discussionmentioning
confidence: 99%